Office paper recyclability: Response to second recycling of fibers - Benitez, Julieta B.; Koga, Mariza E.T.; Otero D'Almeida, Maria L.; Felissia, Fernando E.; Park, Song W; Area, María C. (My University, 2014)
Recyclability is the ability of a material to reacquire the same properties it had originally. Knowledge of the recyclability of commercial paper is a tool for companies, when making decisions on expansions or process modifications. The aim of this work was to verify the recyclability of four printing and writing papers from their physical, mechanical and optical properties after two recycles. Four commercial bond papers were studied, including 3 Eucalyptus kraft from Argentina and Brazil (A, B, C) and a soda-AQ from sugarcane bagasse (D), with different bleaching processes. That papers were repulped and refined using 2 levels of energy at 2 different intensities (1st recycle). Laboratory sheets were produced, and then repulped and refined again (2nd recycle). The behavior of the 2nd recycle pulps and the results of the 1st and 2nd recycles were statistically compared to verify the recyclability of the original papers. It was shown that recyclability, represented by the evolution of properties of the repulped papers, is different in all cases, although it shows a greater similarity among the papers made from eucalyptus kraft pulps than between them and the paper made from soda-AQ pulp from bagasse. This means that the application of fne adjustments in the pulping and bleaching processes may produce substantial differences in the recyclability of the final papers. The bagasse paper required less refining energy to reach its highest level of properties, but they were always poorer than those of the other papers and decreased markedly with recycles. As a general rule, the use of mild conditions in the first recycle (refining at 30° SR with low intensity), allows to achieve a 2nd recycle without signifcant loss of properties.
Reciclabilidad de papeles de oficina: Respuesta a dos reciclos
Keywords: Eucalyptus; Office paper; Physical properties; Recyclability; Recycling; Sugarcane bagasse